Morphometry of Deutero Malay female nose (Faculty of Medicine Universitas Indonesia, 2009)
Aim The objective of this study is to carry out morphometric measurements of the nose, in order to establish norms for the Indonesian as the representation of Asian, specifically for the Deutero Malay sub race. Method A cross sectional study was performed on 126 subjects, recruited from female students of Medical Faculty, the University of Indonesia, Jakarta. Subjects were restricted within Deutero Malay sub race (including ethnic groups of Aceh, Jawa, Sunda, Minangkabau, Riau and Bugis) in 3 generations. Subjects were photographed with digital camera in frontal, left lateral and basal view. Then from the photographs which were stored as JPEG files, linear as well as angular measurements were carried out. Results The intercanthal width is 3.56 cm + 0.27, alar width 4.14 cm + 0.28, length of the nose 4.0 cm + 0.21, pronasion projection 2.29 cm + 0.26 and tip angle 111.5o + 4.4, nasofrontal angle 134.6o + 7.3, nasofacial angle 36.3o + 4.3, nasolabial angle 90.4o + 8.3, and nasion projection 0.43 cm + 0.22. Conclusions The data collected from this study can be used as norms for Deutero Malay cases and will serve as a guide for quick reference, when planning aesthetic or reconstructive rhinoplasties for the Deutero Malay patient. (Med J Indones 2009;18:189-92)